2020
DOI: 10.1210/clinem/dgaa487
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Adrenal Hemorrhage in Coronavirus Disease 2019 Patient: A Case Report

Abstract: Context Bilateral adrenal hemorrhage is a rare condition with potentially life-threatening consequences as acute adrenal insufficiency. Early adrenal axis testing, as well as directed imaging, is crucial for immediate diagnosis and treatment. Coronavirus disease 2019 (COVID-19) has been associated with coagulopathy and thromboembolic events. Case decription A 66-years-old woman presented with acute COVID-19 infection and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 12 publications
2
59
0
6
Order By: Relevance
“…According to patient’s history of recurrent abortions, the presence of antiphospholipid antibody syndrome (APLS) was also suspected and confirmed by specific antibody assays. Hence, authors hypothesized that the combination of both COVID-19 infection and APLS was responsible for adrenal failure [ 97 ]. Another case is a 70-year-old man, with a history of psoriasis, hospitalized with persistent lower back pain resistant to medical treatment.…”
Section: Resultsmentioning
confidence: 99%
“…According to patient’s history of recurrent abortions, the presence of antiphospholipid antibody syndrome (APLS) was also suspected and confirmed by specific antibody assays. Hence, authors hypothesized that the combination of both COVID-19 infection and APLS was responsible for adrenal failure [ 97 ]. Another case is a 70-year-old man, with a history of psoriasis, hospitalized with persistent lower back pain resistant to medical treatment.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 was associated with the flares of pre-existing APS. The complications include bilateral adrenal glands hemorrhage in a 66-year-old female and limb ischemia in another 48-yearold male, both of which were controlled by anticoagulants (58,59). Interestingly, one study revealed 5 (63%) of eight pregnant women with COVID-19 infection fulfilled diagnostic criteria for pre-eclampsia/HELLP syndrome (hemolysis; elevated liver enzymes; low platelet count), perhaps due to overlapping features.…”
Section: Antiphospholipid Antibody Syndrome (Aps)mentioning
confidence: 99%
“…Imaging confirmed a small filling defect in the left renal vein consistent with a non-obstructing thrombus. 5 A further recently published case report describes non-haemorrhagic adrenal infarction in a patient with COVID-19 infection who presented with abdominal pain and hyponatraemia. 6 To our knowledge, we report the first case of a clinically occult unilateral AH to present in a patient with confirmed COVID-19 infection in the absence of abdominal symptoms or clinical signs of adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 98%